Konfliktusok Erdélyben és Dél-Szlovákiában (Szociológiai Szemle, 2024)
All of the six initial hypotheses, concerning the determined nature of the conflict potential deriving from national-ethnic majority and minority existence have been proved. Majority existence makes people less inclined to have conflict-enhancing attitudes towards the minority, whereas minority existence favours the growth of conflict potential in the circle of those concerned. Those belonging to the majority, if they also constitute a majority locally, show greater intolerance towards the minority, they are more inclined to negatively assess the minority (conceiving scapegoats in Transylvania, linguistic intolerance in South Slovakia), and can be characterised by a larger potential of ethnic tension. Hungarians in minority live in the condition of permanent anxiety and threat, hence their sensitivity towards conflict is also greater. If members of the minority constitute a majority locally, then - perhaps due to a greater sense of security offered by majority existence - the signs of tolerance can also be found (in Transylvania they are less inclined towards conceiving scapegoats, they are less ethno-centric in South Slovakia). In this case the consequence in the moderation of conflict potential. Socio-demographic variables do not, or little influence inclinations towards conflict, as they also have no, or little effect on inclinations towards harmony.